Natural horsemanship - Horváth, Tímea; Mészáros, Gyula (Animal welfare, Ethology and Housing Systems (AWETH), 2008)
Natural Horsemanship – the once used and by today completely forgot and unheeded part of horse schooling, that made, makes and can make riding aids invisible.” (Mészáros, 2007). In this short text the basics of the natural horsemanship will be presented on the 10 most important attributes of a horse. The riders’ attention is called to the fact that the horse should be in focus; consequently, the world has to be seen through the eyes of the horse. For this reason the key of naturalness is the right approach to the horses, i.e. while training a horse to achieve the desired results the person must have full knowledge of the horse’s ethology and behaviour patterns.” (Mészáros, 2007).